Upaya Meningkatkan Keterampilan Belajar Siswa SMA Melalui Model Bimbingan dan Konseling Kolaboratif - Ayi Najmul Hidayat (LPPM UNINUS, 2015)
The less succesful of guidance and counseling in high schools is caused by chinless cooperation between the counselor and the counselee on implementing guidance and counseling. The counselee are expected to be able to enhance thinking skills, make decisions, continue education to the higher levels and plunge into the work field. Yet, counselors often interpret mostly counselees are less capable in handling matters. Therefore, counselors need to perform guidance and collaborative counseling in form of encouraging the counselee to participate, take advantage of capabilities, excellence and experience, until they improve their learning skills. These training methods involve discussions, lectures, and demonstrations / practice. One of the training results is enhancing counselors’ spirit to understand and implement the guidance concept and collaborative counseling as well as to join further trainings. The enthusiasm owned by counselors is supporting its success to provide assistance toward the counselee, as well. This training can increase the counselors capabilities to attract the counselee into consultation, and involve them in solving the problem. Guidance and collaborative counseling accordance with the conditions in schools are quite appropriate for handling the problems faced by the counselee.